1989
DOI: 10.1063/1.102053
|View full text |Cite
|
Sign up to set email alerts
|

Inductive conductance measurements in two-dimensional superconducting systems

Abstract: A two-coil mutual-inductance technique for measuring the complex ac response of a two-dimensional (2-D) superconductor to a weak ac magnetic field is described. Analytical and numerical methods are presented which allow extraction of the complex ac conductance of the superconductor from the signal voltage induced in the detection coil by the screening currents flowing in the sample. The method is illustrated by measurements of the ac conductance of a square network of aluminum wires from which the penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 9 publications
0
82
0
Order By: Relevance
“…When these coils are located near the surface of the film, the response, i.e., the complex output voltage V, does not depend on the radius of the film or its properties near the edges. In the reflection technique (Jeanneret et al 1989) an excitation coil (primary) coaxially surrounds a pair of counter-wound pick up coils (secondaries). When there is no sample in the system, the net output from these secondary coils is close to zero since the pick up coils are close to identical in shape but are wound in opposite directions.…”
Section: The Mutual-inductance Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…When these coils are located near the surface of the film, the response, i.e., the complex output voltage V, does not depend on the radius of the film or its properties near the edges. In the reflection technique (Jeanneret et al 1989) an excitation coil (primary) coaxially surrounds a pair of counter-wound pick up coils (secondaries). When there is no sample in the system, the net output from these secondary coils is close to zero since the pick up coils are close to identical in shape but are wound in opposite directions.…”
Section: The Mutual-inductance Techniquementioning
confidence: 99%
“…To measure the complex AC susceptibility in our arrays we used a high-sensitive home-made susceptometer based on the so-called screening method in the reflection configuration (Jeanneret et al 1989, Araujo-Moreira et al 2002, as shown in previous sections. The experimental system was calibrated by using a high-quality niobium thin film.…”
Section: On the Origin Of Dynamic Reentrancementioning
confidence: 99%
“…To explore the properties of the array in the critical region, we measured its complex ac sheet conductance G(ω, T ) at f=1/2 using a SQUIDoperated two-coil mutual inductance technique [9], which allows to probe critical fluctuations over a frequency range covering more than 5 decades (0.1 Hz -10 kHz). At the temperatures of interest (T ∼ = 5K) we estimate that the vortex diffusion…”
mentioning
confidence: 99%
“…M(x) is the mutual-inductance distribution resulting from the geometry of the measuring system. See Jeanneret et al (1989) for specific details on the derivation of this equation. 18 We tested this by using a square-wave signal as our input signal.…”
Section: Measurementsmentioning
confidence: 99%
“…To conduct contactless ac measurements, we use a two-coil mutual-inductance technique similar to that outlined by Jeanneret et al (1989). Our main measurement apparatus consists of a drive coil of radius Rd--0.42 cm and a pair of astatically wound receive coils of radius Rr=0.24 cm which is coaxially mounted within the drive coil (see Fig.…”
Section: Ac Measurementsmentioning
confidence: 99%